The complete mitochondrial genome of the Goniopora djiboutiensis - Fei Tong; WenJing Chen; PiMao Chen; Lu Zhang (Mitochondrial DNA. Part B. Resources, 2019)
In the present study, we determined the complete mitogenome sequence of scleractinia, Goniopora djiboutiensis using Illumina HiSeq platform. The assembled mitogenome was 18,765 bp in length, comprising unique 13 protein-coding genes (PCGs), two ribosomal RNAs, and two transfer RNAs genes of each, showing a typical scleractinia pattern. New phylogenetic analysis upon complete mitogenomics revealed that G. djiboutiensis is most closely related to G. columna, with high bootstrap values. It would provide further insights on the taxonomy and phylogeny of genus Goniopora de Blainville.